Exploring the spatiotemporal effects of urban scale and urban vitality on S&D balance in the Yangtze River Delta, China from 2015 to 2025 - Ke Wang; Qiuxiao Chen (Scientific Reports)
Abstract Analysis of the spatiotemporal trends of urban scale and urban vitality on ecosystem services balance provides an essential basis for regional sustainable development. This study employs the Spatial Durbin Model (SDM), Spatial Autoregressive Model (SAR), and Geographically and Temporally Weighted Regression (GTWR) to effectively capture spatiotemporal associations between urban scale, urban vitality, and ecosystem services supply-demand balance, providing a detailed view of regional variations. The integrated framework combines spatiotemporal analysis, predictive scenario simulation, and importance-performance analysis to quantify and strategize urban impacts on ESs. Results show that urban scale negatively impacts the S&D ratio, while certain urban vitality factors support ecological supply (ESSI) and others enhance ecological demand (ESDI), contributing to a more balanced S&D ratio. Second, the economic priority scenario had the greatest influence on the S&D ratio, reaching − 37.5%. This resulted in Zhejiang Province’s S&D value approaching 1 (the lowest S&D value being 2.044). In Anhui, Jiangsu Province, and Shanghai, the ecological priority scenario had the most impact on the S&D ratio, raising the S&D value to 0.58 ~ 1.057. While urban scale and ecological priority scenarios enhance ES supply in northeastern YRD, helping to balance the S&D ratio, urban vitality and economic priority scenarios complement each other in southwestern YRD by driving ES demand, illustrating regional differences in development strategies.